Pengembangan LKPD Biologi Berbasis Model Problem Based Learning Pada Materi Sistem Pencernaan Untuk Siswa SMA/MA - Siagian, Nurul Hikmah; Rasyidah, Rasyidah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
The purpose of this research is to develop LKPD that uses a problem-based learning approach that satisfies the requirements of validation, practice, and effectivity relation to the digestive system issue. This study applies the 4D model as part of a research and development methodology, however, this study just looks at development. Research instruments include questionnaires and interviews to examine the requirements of educators and learners, and LKPD evaluation forms to verify the accuracy of the media, including validation sheets from subject matter and media experts. Additionally, questionnaires filled out by biology teachers and students are used to measure how practical the LKPD is. Additionally, the effectiveness of the developed LKPD was assessed using pre- and post-tests. Students from class XI IPA 1 MAPN 4 Martubung served as the exam subjects. A teacher and thirty-four students participated in the polling.The study's conclusions showed that (1) the LKPD received 99% of the grade awarded for the media and 84% of the score given for the material in the validity test; (2) With very practical criteria, the practicality test achieved a teacher response score of 96% and a student response score of 88.91%; (3) The effectiveness test showed a high and category of effectiveness with an N-Gain of 0.76. Thus, the PBL-based LKPD that has been developed is suitable for use because it has met the minimum development requirements of validity, practicality, and effectiveness.